AN USABILITY TEST USING THE METHOD EYE TRACKING ON ACADEMIC ONLINE WEBSITE UNIVERSITY MEDAN AREA - Sutrisno Sutrisno; Yudi Daeng Polewangi; Erwandi Rambe (Sean Institute, 2022)
The Academic Online Campus application is an information system used to manage academic data administration. Academic Online Campus websiteMedan Area University found several obstacles such as getting information quickly and the absence of an information assistance center. This study aims to determine the results of usability testing on the Academic Online Campus University of Medan Area website using the eye tracking method. Eye tracking is a method that helps researchers understand visual attention, with eye tracking we can detect where the user is looking, how long they are looking, and the order in which they are looking.This test was carried out by providing several tasks that were carried out by the respondent, to see the success of each task and the respondent's processing time. Then the SUS questionnaire was distributed to determine the level of satisfaction of the respondents. The results showed that the ease of using the Academic Online Campus website with an average level of effectiveness was 77.40% (quite effective), the average efficiency level of using the website was 73.65% (quite efficient), and fstudent satisfaction actors obtained an average score of 70.47 which indicates that the Academic Online Campus website is included in the acceptable category with a Good rating and is ranked C. This means that the Academic Online Campus website has an attractive appearance, displays information needed by students and lecturers, and provide complete and up-to-date information.